PENGINTEGRASIAN TEKNOLOGI MAKLUMAT DAN KOMUNIKASI DALAM PENGAJARAN DAN PEMBELAJARAN DI KALANGAN GURU KEMAHIRAN HIDUP BERSEPADU - Shariff, Anas Redzuan; Puteh, Saifullizam (Online Journal for TVET Practitioners, 2018)
This is a case study on the Integrated Living Skills (ILS) of the secondary schools teachers to review the level of ICT’s integration in the teaching and learning session with the ICT facilities in the school. The review is related to the level of ICT’s integration in the teaching and learning, the level of ICT facilities in schools, the relation between the level of ICT’s integration with the ICT’s facilities upon the implementation of the Integrated Living Skills teacher’s teaching and learning session and the difference in the level of secondary schools in the urban and rural area. This case-study was done quantitatively through the questionnaires as the research instrument distributed to 97 Integrated Living Skills teachers in Kota Tinggi, Johor. The data were analysed to get the mean scores, Pearson correlation and the t-test. The results show that: ILS teachers showed the high level of integration in the teaching and learning session, average ICT’s facilities in the teaching and learning process, there was positively weak significant relation between the level of ICT’s integration in the teaching and learning with the ICT’s facilities among the Integrated Living Skills teachers and the null hypothesis is accepted as it showed no significant difference between secondary school in urban areas and rural areas to the integration of ICT. The level of ICT’s integration in the teaching and learning of the Integrated Living Skills teachers were found to be increased if the ICT facilities is provided in school. However, there are no significant difference between the secondary schools in the urban and rural areas in the integration of ICT in the teaching and learning as the teachers were provided with the ICT’s knowledge and skills in the line with 21st century clasroom learning.